Analysis of e-service quality through online shopping - Nasser, Mohammad Al- (Academic Journals Inc., 2015)
This study investigates the factors that influence the e-service quality through online shopping.E-service quality is the difference between customers’ expectations for service performance priorities the service encounters and their expectations about service performance prior to the service offering.Due to the recent growth in e-service quality in the field of e-commerce, the importance of monitoring and measuring e-service quality has provided value to the virtual world. Perceived risk has been studied in marketing for over 40 years and appears to be an appropriate construct to understand consumer adoption of e-commerce payment systems.The internet’s impact upon the Malaysian market is significant and this has made it convenient for consumers to purchase products/services from the vendor and to go through the product information over the internet. The findings indicate the analysis of e-service quality through online shopping.